2015
DOI: 10.1016/j.yebeh.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired performance on advanced Theory of Mind tasks in children with epilepsy is related to poor communication and increased attention problems

Abstract: Children with epilepsy (CWE) have social difficulties that can persist into adulthood, and this could be related to problems with understanding others' thoughts, feelings, and intentions. This study assessed children's ability to interpret and reason on mental and emotional states (Theory of Mind) and examined the relationships between task scores and reports of communication and behavior. Performance of 56 CWE (8-16years of age) with below average IQ (n=17) or an average IQ (n=39) was compared with that of 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 66 publications
3
22
2
1
Order By: Relevance
“…The inclusion criteria for patients were children with epilepsy (CWE) in mainstream education with presumed genetic or unknown etiology without identifiable structural or metabolic abnormalities. The research program's recruitment strategy has been previously described 9 . At recruitment to the research program a pediatric neurologist classified patients in accordance with the revised terminology proposed by the International League Against Epilepsy (ILAE) [2005][2006][2007][2008][2009].…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria for patients were children with epilepsy (CWE) in mainstream education with presumed genetic or unknown etiology without identifiable structural or metabolic abnormalities. The research program's recruitment strategy has been previously described 9 . At recruitment to the research program a pediatric neurologist classified patients in accordance with the revised terminology proposed by the International League Against Epilepsy (ILAE) [2005][2006][2007][2008][2009].…”
Section: Participantsmentioning
confidence: 99%
“…Few studies have addressed the link between social perceptual skills and behavioural difficulties. Golouboff et al reported impaired fear recognition predicted behavioural problems in a subset of TLE patients, and perceptual theory of mind deficits were shown to correlate with social and attention problems in a heterogeneous patient group with below average IQ 9 . Overall, findings indicate a high degree of individual variability, and deficits not isolated to the social perceptual domain.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that we found a ToM-Q deficit in children with refractory epilepsy, as even children with "epilepsy only" (epilepsy at the benign end of the severity spectrum) have recently been shown to have a ToM deficit (Lew et al, 2015;Lunn et al, 2015). Controlling for VIQ did not eliminate this effect.…”
Section: Children With Refractory Epilepsy Have a Tom Deficitmentioning
confidence: 62%
“…Despite its developmental significance in everyday functioning, research on ToM in paediatric epilepsy patients is scarce. ToM is vulnerable even in children with "epilepsy only" and this cannot be explained by lower intelligence (Lew et al, 2015;Lunn et al, 2015). Furthermore, a later onset of epilepsy is associated with better ToM functioning, whereas antiepileptic drug use is not related to ToM functioning (Lew et al, 2015;Lunn et al, 2015).…”
Section: Theory Of Mind and Surgerymentioning
confidence: 99%
“…são os pioneiros na investigação da ToM na EBICT. Alguns poucos trabalhos investigaram esta função em crianças e adolescentes com outras síndromes epilépticas (Hu, Jiang, Hu, Ma, & Wang, 2016;Lunn, Lewis, & Sherlock, 2015). Investigar a ToM na epilepsia é fundamental, pois as dificuldades nessa função cognitiva estão relacionadas a prejuízos nas habilidades sociais, comunicação, atenção e aprendizagem (Giovagnoli, 2014;Lunn et al, 2015;Schenkel, Marlow-O'Connor, Moss, Sweeney, & Pavuluri, 2008).…”
Section: Funcionamento Executivo Na Ebictunclassified